NATIONAL-CULTURAL DESCRIPTION OF THE IMAGE OF MOTHER IN DIFFERENT CULTURES - Murodova Hafiza Muhammmadjonovna (Modern American Journals, 2025)
This article analyzes the national-cultural interpretation of the image of "mother" in different cultures, the value attitude formed towards the mother in the associative consciousness of the speakers of the language, spiritual and moral approaches. The study provides a comparative analysis of the associative fields of the Uzbek, Russian, Bulgarian and Arab peoples related to the root word "mother", revealing their inextricable connection with their national mentality, worldview and spiritual values. The article, based on the theory of Russian psycholinguistics and associative research, shows the synonymy, metaphorical and associative properties of the word "mother" in different cultures. In Uzbek culture, the image of the mother is interpreted as a symbol of selflessness, love, tolerance, and patience, while in Russian culture it is expressed as a symbol of holiness, kindness, warmth, and loyalty. The Bulgarian people associate the mother with love, selflessness, goodness, and trust. In Arab culture, the religious-metaphorical uses of the word “umm” (for example, Umm al-Qura, Umm al-Kitab) indicate that the mother is perceived in harmony with higher values.
Keywords: Mother image, national-cultural characteristic, associative field, psycholinguistics, mentality, metaphorical interpretation